Power loss minimization assessment of a doubly fed induction generator with variable core resistance for wind turbines operation - Crescent Onyebuchi Omeje; Damian Benneth Nnadi (International Journal of Applied Power Engineering (IJAPE), 2022)
This paper assesses the efficiency level and power loss minimization of a doubly fed induction generator (DFIG). A modified DFIG equivalent circuit with multi-core resistance connected in parallel was adopted. State-space differential equations of the DFIG was developed incorporating iron and copper loss components while a minimum flux linkage that aids in the minimization of the overall losses was derived. Simulation results showed that losses were minimized when the equivalent core resistances were connected in parallel with minimum permissible current flow. The results obtained during a transient disturbance showed that at different core resistance values of Rfe = 0.75Ω and 0.25Ω, different efficiency values of 83.45% and 41.21% were realized. An unconstrained optimization test carried out on the DFIG variable parameters showed that the DFIG power loss model was controllable with a positive definite value of 691.9801 and 2.9156〖e〗^(+5) for the leading principal determinants of the Hessian matrix. All simulation processes were achieved in MATLAB/Simulink 2020.